2015
DOI: 10.1007/s11295-015-0858-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed genes using digital gene expression profiles in Pyrus pyrifolia Nakai cv. Hosui bud release following early defoliation

Abstract: BReturning bloom^is a major problem in the warm pear-producing regions during autumn-winter after the pear harvest and can cause tremendous pear production losses in the following year. The molecular mechanism causing this phenomenon is a mystery. We used high-throughput tag-sequencing (tag-seq) technology to analyze the gene expression profiling of pear (Pyrus pyrifolia Nakai) floral buds at three time points for completely defoliated plants after harvest. A total of 13.2-15.8 million reads were obtained for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…However, growth cessation and bud endodormancy were not clearly distinguished in their study. It is difficult to determine whether plants in their study were in the endodormancy stage or had just ceased growth, because even if the trees ceased growth and formed apical buds, the apical buds might sprout when early defoliation occurs in summer 30 . According to our observations, under natural conditions in Hangzhou, China (30° 06′ N; 119° 55′ E), the bud-break percentage of ‘Cuiguan’ pear ( Pyrus pyrifolia ) under forcing conditions decreased from September and reached its lowest in late October.…”
Section: Endodormancy Induction In Deciduous Fruit Treesmentioning
confidence: 99%
“…However, growth cessation and bud endodormancy were not clearly distinguished in their study. It is difficult to determine whether plants in their study were in the endodormancy stage or had just ceased growth, because even if the trees ceased growth and formed apical buds, the apical buds might sprout when early defoliation occurs in summer 30 . According to our observations, under natural conditions in Hangzhou, China (30° 06′ N; 119° 55′ E), the bud-break percentage of ‘Cuiguan’ pear ( Pyrus pyrifolia ) under forcing conditions decreased from September and reached its lowest in late October.…”
Section: Endodormancy Induction In Deciduous Fruit Treesmentioning
confidence: 99%
“…RNA-seq is a valuable tool for transcriptomic profiling, such as digital gene expression (DGE) technology (Glaser, 2009 ; Wang et al, 2009 ; Asmann et al, 2012 ). Recently, DGE has been used widely to detect differentially expressed genes (DEGs) in crops, such as rice (Ding et al, 2016 ), maize (Eveland et al, 2010 ; Liu et al, 2015 ), cotton (Wei et al, 2013 ) and Brassica (Jiang et al, 2015 ); in woody plants, such as peach (Li et al, 2015 ), orange (Yang et al, 2013 ; Sun et al, 2014 ), pear (Zhang et al, 2015 ), white spruce (Albouyeh et al, 2010 ), and Metasequoia glyptostroboides (Zhao et al, 2015 ); and in orchids, such as cymbidium (Yang and Zhu, 2015 ), Rosa chinensis (Yan et al, 2015 ), and Tagetes erecta (Ai et al, 2016 ). DGE promotes our understanding of the major changes in metabolic processes and enables us to detect DEGs.…”
Section: Introductionmentioning
confidence: 99%
“…Mineral nutrients and carbohydrates play key roles in floral bud differentiation [36,37], and these are dominantly supplied from leaves by the source-sink transport mechanism [38,39]. In pear, sorbitol is the main transportable photo-assimilate, which was confirmed to contribute to flower bud differentiation [40,41]. The present study found that the number of source organs or the sorbitol concentration of buds and phloem sap was significantly lower in wizened bud stems than in normal bud stems (Figures 1C and 8A,C), thereby suggesting that wizened bud occurrence is related to the insufficient supply of sorbitol from source (leaves) to sink (bud) organs, and sorbitol may play a key role in the process of wizened bud formation.…”
Section: Discussionmentioning
confidence: 93%